PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT GARAMA PROPERTY DI JAKARTA SELATAN - Fadilla Swandi, Nurul; Jasmani (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of compensation and work discipline on employee performance at PT Garama Property in Jakarta Selatan. The method used is quantitative. The sampling technique used saturated sampling, namely as many as 62 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are that compensation has a significant effect on employee performance with a determination coefficient value of 50.3% and the hypothesis test is obtained t count > t table or (7.788 > 2.000). Work discipline has a significant effect on employee performance with a coefficient of determination of 41.0% and the hypothesis test is obtained t count > t table or (6.462 > 2.000). Compensation and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 9.869 + 0.416X1 + 0.353X2. The coefficient of determination is 61.3% while the remaining 38.7% is influenced by other factors. Hypothesis testing obtained F count > F table or (46.655 > 2.760).